2006
DOI: 10.1152/ajpheart.00491.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of phospholipase C and diacylglyceride lipase pathway in arachidonic acid release and acetylcholine-induced vascular relaxation in rabbit aorta

Abstract: (ECs). In rabbit aorta, AA is metabolized through the 15-lipoxygenase pathway to form vasodilatory eicosanoids 15-hydroxy-11,12-epoxyeicosatrienoic acid (HEETA) and 11,12,15-trihydroxyeicosatrienoic acid (THETA). AA is released from phosphatidylcholine (PC) and phosphatidylethanolamine (PE) by phospholipase A 2 (PLA2), or from phosphatidylinositol (PI) by phospholipase C (PLC) pathway. The diacylglycerol (DAG) lipase can convert DAG into 2-arachidonoylglycerol from which free AA can be released by monoacylglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 52 publications
2
45
0
Order By: Relevance
“…Singer and Peach (45,46) showed that AA relaxed the rabbit aorta, and these relaxations were inhibited by LO inhibitors. Our laboratory (6,48) also demonstrated that ACh-and AA-induced relaxations of rabbit aorta were blocked by LO inhibitors or antisense oligonucleotides against 15-LO-I.…”
Section: M-h) 317 [M-h-(h 2 O)-(ch 3 Oh)] 299 [M-h-2(h 2 O)-(ch 3 Omentioning
confidence: 90%
See 1 more Smart Citation
“…Singer and Peach (45,46) showed that AA relaxed the rabbit aorta, and these relaxations were inhibited by LO inhibitors. Our laboratory (6,48) also demonstrated that ACh-and AA-induced relaxations of rabbit aorta were blocked by LO inhibitors or antisense oligonucleotides against 15-LO-I.…”
Section: M-h) 317 [M-h-(h 2 O)-(ch 3 Oh)] 299 [M-h-2(h 2 O)-(ch 3 Omentioning
confidence: 90%
“…We have previously shown that AA and ACh cause endotheliumdependent, concentration-related relaxations in Indo-and L-NA-treated aortas (6,36). These relaxations are inhibited by LO inhibitors and antisense oligonucleotides against rabbit 15-LO (6,36,48,49). Thus these relaxations are mediated by a 15-LO metabolite of AA.…”
Section: Furchgott and Zawadzkimentioning
confidence: 91%
“…Moreover, the heat-induced accumulation of PS and the BA-induced enhancement of DAG may play a positive regulatory role in PKC activation and consequently in HS induction, since both PS and DAG are essential cofactors of PKC [64,65], but can be differently affected by the different stressors. 20:4-DAG can be subsequently metabolised by DAG lipase to 20:4-monoacylglycerol (20:4-MAG) [66,67] after which AA can be released through the action of monoacylglycerol lipase or fatty acid amide hydrolase action [68]. AA released by both PLA 2 and PLC-mediated pathways can mediate signal transduction and be recycled via the Lands pathway, whereas a portion can be lost to b-oxidation.…”
Section: Membranes Are Key Determinants Of Cellular Stress Adaptationmentioning
confidence: 99%
“…Arachidonic acid may also be released through PLC-and diacylglycerol lipase-mediated pathway. This pathway was reported to be a source of arachidonic acid in human platelets (Bell et al, 1979), murine macrophages (Moscat et al, 1986), rat pancreatic acini (Hou et al 1996) and rabbit aortae (Tang et al, 2006). U-73122 has been shown to be a selective inhibitor of PLC in human platelets and polymorphonuclear neutrophils (Bleasdale et al, 1990;Smith et al, 1990) There are two types of PLCs: phosphatidylinositolspecific PLC and phosphatidylcholine-specific PLC.…”
Section: Effect Of Rhc-80267 (An Inhibitor Of Diacylglycerol Lipase) mentioning
confidence: 99%
“…Arachidonic acid has been shown to be released mainly by two different pathways: (1) phospholipase A 2 (PLA 2 ) hydrolyzes the sn-2 ester bond of membrane phospholipids, thereby releasing arachidonic acid (Irvine, 1982;Balsinde et al, 2002); (2) phospholipase C (PLC) cleaves the phosphodiester bond, resulting in the formation of diacylglycerol, which can be hydrolyzed by diacylglycerol lipase to yield arachidonic acid (Bell et al, 1979;Irvine, 1982;Moscat et al, 1986;Hou et al, 1996;Tang et al, 2006). Previously, we reported that the brain PLA 2 is involved in the centrally administered melittin (PLA 2 activator)-induced elevation of plasma noradrenaline and adrenaline (Yokotani et al, 2000), and that the brain PLCdiacylglycerol lipase pathway is involved in the centrally administered corticotropin-releasing factor-, argininevasopressin-and bombesin-induced elevation of plasma catecholamines in rats (Okada et al, 2003b;Shimizu et al, 2004Shimizu et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%